“Imaginary homelands”: Henderson the rain king and the spiritual quest - Mohd Nazri, Latiff Azmi; Ramzi B., Mohamed MARROUCHI (2019)
This paper investigates how and why the spiritual quest of Saul Bellow's Henderson the Rain King (1959) enigmatically results in madness. The identity of the American subject should be investigated in the light of his/her restless search of “Other modes of freedom” and imaginary homelands. -Pondering upon this, the researcher realizes that three fundamental questions need to be addressed: What are the aspects of Henderson's spiritual quest? -As a Jewish hero, how could Henderson be associated with quest, victimization and madness? Can one think about identity or identities? To unmask these blind spots, the theme of the quest will be investigated, first. The researcher shall trace Henderson's movement from a material world – New York – to a spiritual and romantic one, Africa. Second, Henderson's failure to cope with the new world and therefore his failure to (re) – construct the identity of the American character will be examined in details. This safely allows us to argue for the madness of the hero. The conclusion is that there is no ‘absolute identity’ to the American subject. Henderson's attempts to re-construct a “new identity” shall be seen in line with poststructuralist premises regarding “difference, multiplicity, other, cultural diversity.”